Feeding frequency, prey acceptance, and natural diet of the mygalomorph spider acanthogonatus centralis goloboff 1995 (Araneae: Nemesiidae) - Pompozzi, Gabriel Alejandro (2018)
The family Nemesiidae is the second most diverse family of Mygalomorphae spiders. Acanthogonatus centralis (Nemesiidae) is commonly found in hilly areas of central Argentina. These spiders are considered generalists due to their basal position in the phylogeny, but little is known about the trophic ecology of the species. Therefore, the objectives of this study were to study some of the species’ predatory traits, such as feeding frequency and prey acceptance, and to assess its natural diet. In addition, two parameters - attack latency and consumption time - were measured for each accepted prey. We found that A. centralis feeds every two days and accepts almost all prey offered. The most accepted prey items were beetle larvae and termites. In fact, termites were attacked faster than any other prey, suggesting they are a suitable prey for these spiders. In regard to the species’ natural diet, we found remains of seven prey items, ants and beetles being the most frequent. In this study, we found that Acanthogonatus centralis is polyphagous since it accepts different kinds of prey.